Activation of the Coagulant Pathway in Cigarette Smokers - Miller, G. J.; Bauer, K. A.; Cooper, J. A.; Rosenberg, R. D. (Thrombosis and Haemostasis, 1998)
The effects of chronic cigarette smoking on the coagulation system were examined in 2964 men aged 50 to 61 years and clinically free of cardiovascular disease. Factor VII activity (VIIc), factor VII antigen (VIIag), prothrombin fragment 1+2 (F1.2), fibrinopeptide A (FPA) and fibrinogen were measured in all participants, and activated factor VII (VIIa), factor IX activation peptide (IX pep) and factor X activation peptide (X pep) in a large sub-sample. The levels of all indices except FPA differed significantly between non-smokers, ex-smokers and current smokers. After adjustment for other conventional cardiovascular risk factors, mean VIIc was raised slightly by 3% in ex-smokers and current smokers as compared with non-smokers, owing to increases in VIIa and VIIag. Plasma IX pep, X pep, F1.2 and fibrinogen concentration were highest in current smokers, intermediate in ex-smokers and lowest in non-smokers. These findings accord with the increased risk of arterial thrombosis in smokers.